Klausa Verbal dalam Cerpen Imraatun Ghalabat al-Syaithan Karya Taufiq al-Hakim (Arabic Syntax Study): Klausa Verbal dalam Cerpen Imraatun Ghalabat al-Syaithan Karya Taufiq al-Hakim (Arabic Syntax Study) - Fadilla, Audryane Anindita; Rohanda, Rohanda; Pauji, Resa Restu (Al-Lisan: Jurnal Bahasa, 2026)
Background: Human communication, whether spoken or written, is fundamentally structured around clauses, with verbal clauses holding particular significance. This is equally true in literary works, where the complexities of verbal clauses given their varied types and functions are prominently displayed. Consequently, investigating these clauses is essential for a deeper comprehension of syntactic structures. Aims: This study aims to identify the types of verbal clauses based on their internal structure and their position within sentences, and to determine their functions in the source text. Methods: Employing a qualitative content analysis method, this research focuses on verbal clauses as the unit of analysis. The data source is the short story "Imraatun Ghalabat Al-Syaithan," from Taufiq Al-Hakim's anthology Arinillah. Data were collected through scrutinizing and note-taking techniques, and subsequently analyzed using translational and permutational methods. Results: The analysis revealed two primary categorizations. Based on internal structure, both complete and incomplete clauses were identified. Based on syntactic position, verbal clauses were found that either hold a grammatical position (al-jumlatu-lati laha mahallun minal-'irab) or are syntactically independent (al-jumlatu-lati la mahalla laha minal-'irab). Functionally, the verbal clauses served to express renewal and occurrence (li tajaddud wa huduts), continuous renewal (li tajaddud istimrariyah), and permanence/stability (li tsubut). Implications: This study underscores the critical role of syntactic units in shaping meaning and ensuring effective message delivery. A nuanced understanding of clauses and syntax is fundamental for achieving grammatically accurate and precise interpretation of sentences, both in literary analysis and broader linguistic study.